Traços do tempo: a representação das experiências afro-brasileiras em “Encruzilhada” (2016) e “Angola Janga” (2017), de Marcelo D’Salete - Lima, Gabriela Ferreira (Universidade Federal de São Carlos, 2026)
This research aimed to analyze how the graphic novels Encruzilhada (2016) and Angola Janga: Kingdom of Runaway Slaves (2017), by Marcelo D’Salete, represent the experiences of racism and Black resistance in Brazil. We started from the premise that Black arts and aesthetics in general, and the graphic novels selected here specifically, are important contributions to understanding the social and cultural dynamics that shaped the Afro-Brazilian experience. Our investigation starts from the following sociological problem: in what way and with what tools do the comic books Encruzilhada and Angola Janga: Kingdom of Runaway Slaves, by Marcelo D’Salete, represent the experiences of racism and black resistance in Brazil? More specifically, we sought to: a) sociologically analyze the production process and the meanings of the artistic and narrative choices present in Angola Janga and Encruzilhada; b) explore how the interpretations and meanings deposited by the author in both productions challenge the predominant narratives about Afro-Brazilian history and experiences; and c) investigate how the works Encruzilhada and Angola Janga develop the categories of time and memory to illustrate Afro-Brazilian resistance and struggle. This research adopted a qualitative approach, using iconography and content analysis to explore the visual and narrative elements present in the works. In addition, an in-depth interview was conducted with the author Marcelo D'Salete. Overall, the research demonstrates that Encruzilhada (2016) and Angola Janga: Kingdom of Runaway Slaves (2017) constitute visual counter-narratives that reconfigure the representation of Afro-Brazilian experiences by moving black individuals from the historical condition of objects of violence to the position of agents of memory and resistance. Through aesthetic and narrative choices, D’Salete articulates the past and present, highlighting the continuities of the racist structures of Brazilian society and, at the same time, the strategies of black resistance.
Traces of time: the representation of afro-brazilian experiences in “Encruzilhada” (2016) and “Angola Janga: Kingdom of Runaway Slaves” (2017), by Marcelo D’Salete
Keywords: Representação; História em quadrinhos; Marcelo D’Salete; Racismo; Resistência negra; CIENCIAS HUMANAS::SOCIOLOGIA; 10. Redução das Desigualdades